DARI SAMPAH MENJADI EMPATI: PERAN PROGRAM "PISA MERAH" DALAM PEMBENTUKAN KARAKTER SOSIAL-EMOSIONAL ANAK DI TK ‘AISYIYAH BUSTANUL ATHFAL JAJAG - Siti Hamidah; Sholehah Yuliati; Daroe Iswatiningsih (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
The development of socio-emotional competence is a crucial aspect in Early Childhood Education (PAUD) often integrated with character education. This article examines the implementation of the "PISA Merah" (Pilah Sampah Menjadi Rupiah/Sorting Waste into Rupiah) innovation at TK ‘Aisyiyah Bustanul Athfal Jajag as a medium to foster socio-emotional abilities in early childhood. This program not only focuses on environmental management and entrepreneurship education but significantly cultivates empathy, care for others, and a spirit of collaboration in children. Through concrete activities of sorting waste and converting it into scholarship funds for less fortunate friends, "PISA Merah" creates a holistic learning experience, shaping environmentally and socially conscious character from an early age. This research aims to describe the design, implementation, and observed results of the "PISA Merah" program, highlighting its unique contribution to socio-emotional development.